IMPLEMENTASI MEDIA PEMBELAJARAN AUDIO VISUAL DI MADRASAH IBTIDAIYAH NEGERI 6 JEMBER - Efendi, Arfan; Sutomo, Moh.; Mashudi, Mashudi (PGMI Department of Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia, 2023)
The implementation of audio-visual learning media is very good for learning in madrasah, because students learn. This implementation is not only to attract attention so that students are able to pay attention to what material is in it, but the implementation of this learning media is to improve their memory through audio-visual learning. As according to Hamalik (Atin Fatimah 2019: 23) there are three factors that affect the success of a learning media implementation, namely: support from the head of the madrasah, peer teacher support, and internal support in the classroom. This implementation will not work if it is only driven by one factor such as the teacher, but everything will work if all are able to encourage and influence each other to keep running well an audio-visual learning media